Evaluation of febrile seizures in children infected with SARS-CoV-2 Omicron variant in Yunnan, China: a multi-center, retrospective observational study - Liu, Hai-feng; Lu, Rui; Yang, Jian; Xiang, Mei; Ban, Deng; Yang, Jia-wu; Guo, Zheng-hong; Yuan, Ting-yun; Fu, Hong-min (Frontiers in Pediatrics, 2023)
Background：The SARS-CoV-2 Omicron variant was reported to be linked to febrile seizures (FSs), but studies on FSs in children with Omicron infection remain relatively scarce, especially in the Chinese population. This study aimed to investigate the characteristics of children diagnosed with Omicron infection with FSs in Yunnan, China, and evaluate the potential association between FSs and Omicron infection. Methods：This study was conducted at four hospitals in Yunnan from December 8, 2022, to January 8, 2023, and consisted of 590 pediatric subjects. According to clinical characteristics, 85, 129 and 376 subjects were divided into the FS-only, Omicron-FS, and Omicron-only groups, respectively. Demographic, clinical and laboratory data were retrospectively collected for analysis. This is a provisional file, not the final typeset article Results：The incidence of FSs in children with Omicron infection was 25.5% (129/505). Older age, stronger male predominance, as well as lower proportions of prior history and family history of seizures were observed in Omicron-FS and Omicron-only groups than in FS-only group, but there were no differences in these four above-mentioned events between these two Omicron-related groups.Compared to FS-only group, Omicron-FS group also had a shorter fever-to-seizure onset duration and more frequent seizures during a single course of fever. Moreover, higher levels of IL-6, TNF-α and ferritin as well as decreased counts of leukocytes and lymphocytes were confirmed in Omicron-FS group than in FS-only and Omicron-only groups. Regarding COVID-19 vaccination status, Omicron-FS group revealed a higher proportion of unvaccinated children and a lower proportion of three-dose vaccination than Omicron-only group. As for clinical outcomes, proportions of mechanical ventilation and intensive care unit admission observed in the two Omicron-related groups were notably higher than those in FS-only group. Meanwhile, Omicron-FS group showed the longest length of hospital stay, followed by Omicron-only group and FS-only group, in order. Finally, all patients but one who died of fulminant myocarditis had been successfully discharged. Conclusions：The incidence of FSs in children with Omicron infection was 25.5% in Yunnan. FSs might be a clinical sign deserving more attention in children with Omicron infection. Furthermore, COVID-19 vaccination is likely to provide effective protection against Omicron-related FSs in children.